2011
DOI: 10.1007/s11814-010-0403-4
|View full text |Cite
|
Sign up to set email alerts
|

Flow behavior of wakes in a three-phase slurry bubble column with viscous liquid medium

Abstract: Flow behavior of wakes has been investigated in a three-phase slurry bubble column of 0.102 m ID and 1.5 m in height. The dependence of wake characteristics such as rising velocity, frequency, holdup and equivalent size on the operating variables was examined by employing an electric resistivity probe method. The gas velocity, liquid viscosity and solid content in the slurry phase were chosen as independent parameters. The rising velocity of wake region increased with an increase in the gas velocity (4.0-12.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The voltagetime signals, corresponding to the pressure-time signals, were processed by a data acquisition system (NI cDAQ-9205) and a personal computer at a rate of 1000 Hz. The total sample length was longer than 30,000 data [16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…The voltagetime signals, corresponding to the pressure-time signals, were processed by a data acquisition system (NI cDAQ-9205) and a personal computer at a rate of 1000 Hz. The total sample length was longer than 30,000 data [16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the behavior of liquid field of velocity, Li et al [29] showed that the liquid velocity, which increases with increasing the gas superficial velocity, is influenced by the particle concentration slightly and is higher in the core of larger reactors compared to the smaller ones. Also, Lim et al [43] claimed that the rising velocity of wakes and their equivalent sizes increases with increasing the liquid viscosity (1.0-50.0 mPa s), gas velocity (0.04-0.12 m s -1 ) as well as particle concentration (0-25 wt %). Lim et al [43] also reported that the wakes' holdup and frequency increase with increasing the velocity of gas while they decrease with increasing the particle concentration and liquid viscosity.…”
Section: Flow Regimementioning
confidence: 99%
“…Also, Lim et al [43] claimed that the rising velocity of wakes and their equivalent sizes increases with increasing the liquid viscosity (1.0-50.0 mPa s), gas velocity (0.04-0.12 m s -1 ) as well as particle concentration (0-25 wt %). Lim et al [43] also reported that the wakes' holdup and frequency increase with increasing the velocity of gas while they decrease with increasing the particle concentration and liquid viscosity. Similarly, Abdulah [25] reported that in cylindrical slurry bubble column (CSBC) and trapped slurry bubble column (TSBC), particles are distributed along the column longitude more uniformly for a higher value of gas velocity and particle concentration.…”
Section: Flow Regimementioning
confidence: 99%